Number of expeditioners undergoing formal environmental training - MULLIGAN, MARY (hasPrincipalInvestigator); MULLIGAN, MARY (processor); Australian Antarctic Data Centre (publisher)
This indicator is no longer maintained, and is considered OBSOLETE. INDICATOR DEFINITION The number of personnel undergoing formal training in environmental protection and management for participation in the Australian Antarctic Program (AAP) TYPE OF INDICATOR There are three types of indicators used in this report: 1.Describes the CONDITION of important elements of a system; 2.Show the extent of the major PRESSURES exerted on a system; 3.Determine RESPONSES to either condition or changes in the condition of a system. This indicator is one of: PRESSURE RATIONALE FOR INDICATOR SELECTION Protection of the Antarctic environment is a goal and responsibility set down by international agreements such as the Antarctic Treaty and Madrid Protocol, and additionally by the Australian Government. In order to meet this goal, personnel who participate in the Australian Antarctic Program (AAP) have been informed of their responsibilities for environmental protection and management as part of the expeditioner induction process. Since the 2001/02 season, the Australian Antarctic Division (AAD) has required expeditioners to undertake a formal training program in which their collective and individual responsibilities for environmental protection and management are outlined and discussed. This program consists of environment induction sessions held at the AAD headquarters and practical sessions held at the AAD's field training facility. From the 2003/04 season onwards, it is anticipated that expeditioners will also be required to undergo assessment following this training. This indicator offers a method for quantifying and monitoring the level of expeditioner awareness of environmental issues, and the skills with which they work toward the goals of environmental protection and management. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Australian Antarctic and Subantarctic stations and field camps. Frequency: Annual Measurement technique: Data for this Indicator is routinely collected by the AAD's Operations Branch. RESEARCH ISSUES The environment training program will be reviewed regularly to ensure that training is effective in meeting the goal of protecting the Antarctic environment. Feedback from expeditioners participating in the training program and from Station Management in Antarctica is integral to the process of review and improvement. Expeditioners travelling to Antarctica will be subject to formal assessment following completion of the environment training program. LINKS TO OTHER INDICATORS SOE Indicator 47 - Number and nature of incidents resulting in environmental impact SOE Indicator 48 - Station and ship person days SOE Indicator 50 - Volume of wastewater discharged from Australian Antarctic Stations SOE Indicator 51 - Biological Oxygen Demand (BOD) of wastewater discharged from Australian Antarctic Stations SOE Indicator 52 - Suspended solids (SS) content of wastewater discharged from Australian Antarctic Stations SOE Indicator 53 - Waste returned to Australia SOE Indicator 54 - Amount of waste incinerated at Australian stations SOE Indicator 55 - Number of known contaminated sites in the Australian Antarctic Territory SOE Indicator 56 - Monthly fuel usage of the generator sets and boilers SOE Indicator 57 - Monthly total of fuel used by station incinerators SOE Indicator 58 - Monthly total of fuel used by station vehicles SOE Indicator 59 - Monthly electricity usage SOE Indicator 60 - Total helicopter hours SOE Indicator 61 - Total potable water consumption at Australian Antarctic Stations SOE Indicator 69 - Resources committed to environmental issues